STUDI EMPIRIS : PERAN IKLIM KERJA KREATIF DAN KESESUAIN TUJUAN TERHADAP PEMENUHAN KONTRAK PSIKOLOGIS SERTA DAMPAKNYA PADA KINERJA RELIGIUS - Ali Jufri (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
The creation of a positive climate must be carried out by an organization to support the development of the creativity of people who are members of the organization. The creation of a climate that supports creativity, especially in improving the performance of individuals and organizations / companies, of course, must bring about a match between goals between individuals and organizations. The organization must also pay attention to the rights of its members in addition to demanding full obligations. Fulfillment and violation of psychological contracts will have an impact on individual performance in general where the majority of Indonesia's population has a religious side that is still high. Religious performance is a hope and belief that what we do has a religious value. Thus the organization must be able to build and provide complete facilities in supporting the religious side of the members of the organization. The focus of this writing is how the creative work climate and goal congruence for the fulfillment of psychological contracts and their impact on religious performance. This writing uses relevant literature studies. This research is expected to be empirical study capable of presenting a picture of the creative work climate and Goal Congruence able to give effect to the fulfillment of psychological contracts and their impact on improving the performance of Religious employees.